2002
DOI: 10.1109/55.974794
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN/GaN HEMTs on (111) silicon substrates

Abstract: AlGaN/GaN HEMTs on silicon substrates have been fabricated and their static and small-signal RF characteristics investigated. The AlGaN/GaN material structures were grown on (111) p-Si by LP-MOVPE. Devices exhibit a saturation current of 0.91 A/mm, a good pinchoff and a peak extrinsic transconductance of 122 mS/mm. A unity current gain frequency of 12.5 GHz and max =0.83wereobtained.Thehighestsaturationcurrentreported so far, static output characteristics of up to 20 V and breakdown voltage at pinchoff higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 10 publications
2
40
0
1
Order By: Relevance
“…K) for nitride devices. 10,11 Different orientations of Si were studied for GaN HEMT by various research groups to investigate efficient power device platforms. Boulay et al 12 demonstrated GaN HEMTs on (001) oriented Si substrate for microwave power application.…”
Section: Introductionmentioning
confidence: 99%
“…K) for nitride devices. 10,11 Different orientations of Si were studied for GaN HEMT by various research groups to investigate efficient power device platforms. Boulay et al 12 demonstrated GaN HEMTs on (001) oriented Si substrate for microwave power application.…”
Section: Introductionmentioning
confidence: 99%
“…An 800 nm GaN buffer layer is followed by a 6 nm thick undoped AlGaN spacer, 20 nm Si-doped carrier supply layer, and 6 nm un- /Vs, respectively. Details of growth and device fabrication are given elsewhere [4]. Device processing consists of conventional HEMT fabrication steps.…”
Section: Device Fabricationmentioning
confidence: 99%
“…Recently Si has been found a useful alternative because of its low cost and good thermal conductivity. AlGaN/GaN/Si HEMTs with unity current gain frequencies comparable to those known for devices using sapphire and SiC substrates have been reported [1]. In contrast to sapphire the electrical conductivity of the Si substrate allows the application of a voltage at the back side of the devices through a substrate contact.…”
mentioning
confidence: 92%
“…Many concur that most of the reliability-limiting mechanisms and issues are related to the presence of defect states in the forbidden band-gap of GaN, and the subsequent performance degradation associated with such defects. [3][4][5][6][7][8] Drain-current transient analysis experiments have helped shed light on the degradation observed in switching performance, often manifesting in AlGaN/GaN HEMTs as gate lag, drain lag and current collapse. 9,10 The collapse is attributed to electron trapping comprised of lateral and vertical components.…”
mentioning
confidence: 99%